Financing and delivering early childhood education and childcare across levels of government - Dougherty, Sean (OECD Publishing, 2023)
This paper explores how Early Childhood Education and Childcare (ECEC) can be more effectively financed and delivered to promote human capital development, economic growth and well-being. It discusses evidence showing that quality ECEC contributes to better education outcomes and higher future earnings, particularly for socio-economically disadvantaged children. Yet it identifies challenges in delivering ECEC services, including uneven coverage and lack of affordability in many OECD countries, necessitating intergovernmental fiscal co-operation. In the wake of the COVID-19 pandemic's disruptive effects on children's learning and future GDP, the paper underscores the urgent need for effective policy interventions. These include augmenting public spending, implementing equitable fiscal governance models, enhancing the affordability of services and establishing robust monitoring systems. By addressing these issues, the paper posits that we can ensure equitable access to high-quality ECEC and fortify the resilience of our education systems for future generations
Keywords: Finance and Investment; Governance; Economics